The internal migration patterns of the foreign-born and native born populations in the United States : 1975-80 and 1985-90 - Rogers, Alan; Henning, S.
tbls.
pp. 403-429
Keywords: Migración Interna; Siglo XX; Estados Unidos de America; Extranjeros